Selective control of fcc and hcp crystal structures in Au–Ru solid-solution alloy nanoparticles - Quan Zhang (Nature Portfolio, 2018)
The crystal structure of a solid-solution alloy is generally determined by its elemental composition, limiting synthetic control over the alloy’s properties. Here, the authors are able to selectively control the crystal structure of Au–Ru alloy nanoparticles by rationally tuning the reduction speed of the metal precursors.